"The fruits are very good and inexpensive": Natural history and religious ideology in the book Shaarei Yerushalayim - Shemesh, Abraham O. (HTS teologiese studies, 2020)
The book Shaarei Yerushalayim , written by R. Moshe Reicher, contains contemporary information on 19th-century Eretz Israel. Reicher perceived his compilation as a religious cultural moderator between the Holy Land and the Jews in the Diaspora, in which he reported to the Jews of Galicia on various aspects related to the land. This article discusses his descriptions of local food crops and the messages he attempted to convey to his readers through botanical means. Reicher describes some 70 species of fruits and vegetables that were available in Jerusalem’s markets. The occupation with local fruits is part of a ‘covert campaign’ for Eretz Israel and Jerusalem. Reicher tells his listeners about the good cheap local fruits; he stresses their uniqueness and describes their qualities and the dishes prepared from them, and also compares them with the crops in Galicia.